A new approach for evaluating the sustainability of raw materials substitution based on embodied energy and the CO2 footprint. (20th September 2017) - Bontempi, Elza
Abstract: The aim of this paper is to propose a simplified method of quantifying the environmental sustainability of raw materials substitution. This method is based on the use of two parameters that account for the energies and emissions involved in the formation of a material. The embodied energy and CO2 footprint are used to define a SUB-RAW index, which is used to compare the environmental performances of selected materials. This method is applied to a real case of stabilized municipal solid waste incineration fly ash using COSMOS (acronym of COlloidal Silica Medium to Obtain Safe inert) technology. The collected COSMOS material can substitute for natural resources (e.g., calcite and talc) as filler in polypropylene composites. This recovered material shows a mean embodied energy of 0.82 MJ/kg and mean CO2 footprint of 0.02 kg/kg. The SUB-RAW index, which is very close to zero when comparing COSMOS and calcite, establishes two materials' equivalence regarding the energies and emissions involved in their production. Graphical abstract: Highlights: A new approach to quantify the sustainability of the raw materials substitution is presented. On the basis of the proposed SUB-RAW index a substitute to natural fillers is suggested. The reported example allows to reconsider waste incineration as a recovery option.